THE ANALYSIS OF THE MAIN WORK DATA IN THE MOSCOW CITY BURN CENTER AFTER REMODELING - A. S. Yermolov; S. V. Smirnov; N. A. Karasev; B. L. Kurilin; E. V. Kislukhina; I. V. Kiselevskaya-Babinina; V. A. Vasilyev (Неотложная медицинская помощь, 2016)
The article reports the activity of the Burn Center of the N.V. Sklifosovsky Research Institute for Emergency Medicine. We present comparative data on changes in the structure of patients with a burn injury for the past 20 years, and indicators of clinical outcomes over time.